Life-Course Trauma and Later Life Mental, Physical, and Cognitive Health in a Postapartheid South African Population: Findings From the HAALSI study. (24th March 2020) - Payne, Collin F.; Mall, Sumaya; Kobayashi, Lindsay; Kahn, Kathy; Berkman, Lisa
Objective: To investigate the relationships between exposure to life-course traumatic events (TEs) and later life mental, physical, and cognitive health outcomes in the older population of a rural South African community.Method: Data were from baseline interviews with 2, 473 adults aged ≥40 years in the population-representative Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa (HAALSI) study, conducted in 2015. We assessed exposure to 16 TEs, and used logistic regression models to estimate associations with depression, post-traumatic stress disorder (PTSD), activities of daily living disability, and cognitive impairment.Results: Participants reported an average of 5 ( SD = 2.4) TEs over their lifetimes. Exposure was ubiquitous across sociodemographic and socioeconomic groups. Trauma exposure was associated with higher odds of depression, PTSD, and disability, but not with cognitive health.Discussion: Results suggest that TEs experienced in earlier life continue to reverberate today in terms of mental health and physical disability outcomes in an older population in rural South Africa.